Social Responsibility and Institutional Image in a Public University in Peru - Huapaya-Capcha, Yoselin Andrea; Shiguay Guizado, Giomar Arturo; Abarca Pizarro, Oscar Florentino; Colán Hernández, Bryam Alejandro (Journal of Interdisciplinary Studies in Education, 2026)
Grounded in stakeholder and institutional theories, this study examines the relationship between university social responsibility (USR) and students’ perceptions of institutional image at a public university in Peru. Using a quantitative, correlational design, data were collected from 134 undergraduate students in the Faculty of Social Sciences and Humanities during the 2024–II academic cycle. A structured Likert-scale questionnaire measured perceived USR practices and institutional image, and data were analyzed using Spearman’s correlation. The results revealed a strong and statistically significant positive association between USR and institutional image (rₛ = .762, p < .01), indicating that socially responsible practices are closely linked to how students evaluate institutional reputation. These findings extend existing literature by providing empirical evidence from a resource-constrained public university setting in Latin America, where research remains limited.